Negotiation Training in Business and Management: A Systematic Exploration of the Previous Works - Suryanto, Crista Fialdila; Hermawan, Pri (Integrasi Sains Media, 2023)
The demand for negotiation training has grown steadily, driven by the need to thrive in an ever-changing business landscape. Numerous studies have been conducted to identify effective approaches to negotiation training. However, the pace of development in negotiation training has not kept up with the increasing demand. This research aims to shed light on current trends in negotiation training research to identify gaps that can be addressed through further investigation. In order to explore this topic, a comprehensive examination was conducted using the Scopus database, resulting in the selection of 39 journal articles for further analysis. The findings of this review reveal several gaps in the existing literature, particularly concerning the integration of information and communication technology (ICT) in negotiation training. Furthermore, the review highlights a tendency for negotiation training to remain static, lacking the ability to capture and provide feedback on the dynamic changes during the negotiation process.